2022
DOI: 10.3389/fcomp.2022.791704
|View full text |Cite
|
Sign up to set email alerts
|

“Alexa, You're Really Stupid”: A Longitudinal Field Study on Communication Breakdowns Between Family Members and a Voice Assistant

Abstract: In this paper, we present the results of our long-term study on use of a voice assistant (Amazon Alexa via Amazon Echo Dot) in nine families with children and no previous experience with this technology. The study was conducted over the course of 5 weeks during which the families could interact with the device freely. Three house visits were made to collect empirical data from the adult participants in form of questionnaires. Additionally, conversational data from log files of the voice assistant were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Nevertheless, about half of the participants felt that both parties, i.e., themselves and the robot, were responsible for the failed interaction. Similar attributions have been found in other studies [21]. Mavrina and colleagues found that participants attributed communication breakdowns least to themselves and then to the voice assistant [21].…”
Section: The Influence Of the Robot's Response Patternsupporting
confidence: 78%
See 2 more Smart Citations
“…Nevertheless, about half of the participants felt that both parties, i.e., themselves and the robot, were responsible for the failed interaction. Similar attributions have been found in other studies [21]. Mavrina and colleagues found that participants attributed communication breakdowns least to themselves and then to the voice assistant [21].…”
Section: The Influence Of the Robot's Response Patternsupporting
confidence: 78%
“…Similar attributions have been found in other studies [21]. Mavrina and colleagues found that participants attributed communication breakdowns least to themselves and then to the voice assistant [21]. In their study, an option to attribute the breakdown to the programmer was included, to whom the errors were most frequently attributed.…”
Section: The Influence Of the Robot's Response Patternsupporting
confidence: 70%
See 1 more Smart Citation
“…After testing the reliabilities and validities of the measurement model via Cronbach alpha coefficients (i.e., perceived artificiality = 0.920; perceived intelligence = 0.928; psychological ownership = 0.937; interface flow experience = 0.902; customer satisfaction = 0.926; and customer loyalty = 0.932), confirmatory factor analysis (i.e., model fit indices: chi‐square = 572.066, degree of freedom = 174, p < .001, NFI = 0.927, TLI = 0.937, CFI = 0.948, RMSEA = 0.082; standardized factor loadings of all measures that ranged from 0.802 to 958 for the convergent validity; see Table 2), and a correlation analysis (i.e., comparison of values of calculated average variance extracted with correlation values between the constructs for the discriminant validity; see Table 3), respectively, the authors conducted structural equation modeling to answer the research question via an empirical approach, investigating the conceptually proposed relationships among the constructs from the research question (i.e., model fit indices: chi‐square = 681.955, degree of freedom = 178, p < .001, NFI = 0.913, TLI = 0.922, CFI = 0.934, RMSEA = 0.081). During this data analytic stage, two behavioral characteristics, namely length of VAD ownership and usage frequency, were considered as control variables due to their potential impacts on users' psychological ownership and flow experiences (Mavrina et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In my opinion, my artificial intelligence-enabled voice assistant device appears fake. control variables due to their potential impacts on users' psychological ownership and flow experiences (Mavrina et al, 2022).…”
Section: Artificialitymentioning
confidence: 99%